Telling Stories about Post-war Britain: Popular Individualism and the 'Crisis' of the 1970s. (3rd March 2017) - Robinson, Emily; Schofield, Camilla; Sutcliffe-Braithwaite, Florence; Thomlinson, Natalie
Abstract: This article argues that, by the 1970s, people in Britain were increasingly insistent about defining and claiming their individual rights, identities and perspectives. Using individual narratives and testimonies, we show that many were expressing desires for greater personal autonomy and self-determination. We suggest that this was an important trend across the post-war decades, and of particular importance to understanding the 1970s. This popular individualism was not the result of Thatcher; if anything, it was a cause of Thatcherism. But this individualism had multiple political and cultural valences; desires for greater individual self-determination, and anger with the 'establishment' for withholding it, did not lead inexorably to Thatcherism. There were, in fact, some sources for, and potential outlets for, popular individualism on the left—outlets that explicitly challenged class, gender and racial inequalities. With this, we suggest the possibility of a new meta-narrative of post-war Britain, cutting across the political narrative that organizes post-war British history into three periods: social democracy, 'crisis' and the triumph of 'neoliberalism'. The 1970s was a key moment in the spread of a popular, aspirational form of individualism in post-war Britain, and this development is critical to our understanding of the history of the post-war years.